“I had to start from nothing”: The history of school and career guidance and counselling in Iceland from 1950– 2000 - Vilhjálmsdóttir, Guðbjörg (Menntavísindasvið Háskóla Íslands, 2016)
The history of policy making in school and career guidance in Iceland from its beginnings in the 1950s to the year 2000 is the focus of this research. Legislation and directives at different levels in the education system are described over a long period of time, as well as ministerial reports. These documents tell us that policy makers have been interested in the career development of citizens, and hence their welfare in education and work.Another research focus was the contribution of three pioneers of career guidance in Iceland: Ólafur Gunnarsson (1917?1988), Stefán Ólafur Jónsson (b. 1922) and Gerður G. Óskarsdóttir (b. 1943). They all worked at the Ministry of Education for shorter or longer periods and had training in guidance or counselling psychology. All three were authors of teaching materials in career education. Gerður led the ministerial project or campaign from 1989–1991 as an assistant to the Minister of Education and his chief advisor in educational affairs.Another related focus point of this research is the slow emergence of professionalisation in guidance and counselling; the history of school counselling and career education has had its highs and lows. The question is what fuels development in the making of a new profession and what hinders it? An example of a hindrance in the development of guidance is from the year 1973. Career education was by then quite developed in lower secondary schools. The development of career education ended quite abruptly in 1974 due to new legislation for the compulsory school (I. grunnskóli) that placed no emphasis on career education. This legislation also led to structural changes in the schooling of young adolescents and abolished the curriculum on career education. The draft preceding this legislation in 1974 presented a guidance system, where 26 guidance counsellors would be of service to young adolescents in the compulsory school. Parliament removed this guidance system from the draft for financial and ideological reasons, and it was only 20 years later ...